The end of children? : changing trends in childbearing and childhood - Allan, Graham, 1948-; Lauster, Nathanael Thomas, 1972- (UBC Press, 2012)
In developing countries, concerns about declining fertility rates are matched only by fears that childhood is being destroyed by modern parenting practices. This timely volume brings together scholars from multiple disciplines to provide a more balanced, less alarmist perspective on the meanings and implications of these developments. Contrary to predictions about the end of children and the end of childhood, these investigations of developments in Canada and the United States, and to a lesser extent elsewhere in the world, show that fertility rates and ideas about children and childhood are not uniform but rather vary around the globe based on factors such as time, culture, class, income, and age. By exploring the influences that inform when and why people have children and how they choose to raise them, The End of Children? opens a new dialogue on the idea and place of children in modern society.